Imaging Plasmonic Fields with Atomic Spatiotemporal Resolution - Li, Jianxiong; Saydanzad, Erfan; Thumm, Uwe (My University, 2018)
We propose a scheme for the reconstruction of plasmonic near fields at isolated nanoparticles from infrared-streaked extreme-ultraviolet photoemission spectra. Based on quantum-mechanically modeled spectra, we demonstrate and analyze the accurate imaging of the IR-streaking-pulse-induced transient plasmonic fields at the surface of gold nanospheres and nanoshells with subfemtosecond temporal and subnanometer spatial resolution.